2011
DOI: 10.1084/jem.20101947
|View full text |Cite
|
Sign up to set email alerts
|

Ebf1 or Pax5 haploinsufficiency synergizes with STAT5 activation to initiate acute lymphoblastic leukemia

Abstract: STAT5 is abnormally activated in patients with acute lymphoblastic leukemia, and increased STAT5 activation synergizes with PAX5 and EBF1 to induce disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
115
0
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 147 publications
(132 citation statements)
references
References 77 publications
8
115
0
6
Order By: Relevance
“…Interestingly, STAT5 over-activation and PAX5 haplo-insufficiency have been described as synergistic players to initiate ALL [28, 32]. In the present study we demonstrated that both these aberrancies are not only necessary to drive leukemia, but they are a direct consequence of the expression of the PAX5 fusion protein, which can a) repress the activity of endogenous PAX5 [11] and b) activate STAT5 through LCK (Figure 6).…”
Section: Discussionsupporting
confidence: 58%
“…Interestingly, STAT5 over-activation and PAX5 haplo-insufficiency have been described as synergistic players to initiate ALL [28, 32]. In the present study we demonstrated that both these aberrancies are not only necessary to drive leukemia, but they are a direct consequence of the expression of the PAX5 fusion protein, which can a) repress the activity of endogenous PAX5 [11] and b) activate STAT5 through LCK (Figure 6).…”
Section: Discussionsupporting
confidence: 58%
“…EBF1 is essential for normal B cell maturation, and genetic disruption of EBF1 contributes to leukemogenesis 26,27 . A previous study found consistent loss of EBF1 expression in a small CLL cohort 28 .…”
Section: Resultsmentioning
confidence: 99%
“…To date, only haploinsufficiency of PAX5 was shown to be important for induction of leukemia in an activated STAT5 B ALL mouse model (80). …”
Section: B Cell All Modelsmentioning
confidence: 99%